2008
DOI: 10.1111/j.1538-7836.2007.02857.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors and venous thromboembolism: a long‐term follow‐up study of Swedish men

Abstract: See also Tosetto A. Association or causation: the Janus face of observational research. This issue, pp 555-7.Summary. Background: The link between psychosocial factors and coronary heart disease is well established, but although effects on coagulation and fibrinolysis variables may be implicated, no population-based study has sought to determine whether venous thromboembolism is similarly related to psychosocial factors. Objective: To determine whether venous thromboembolism (deep vein thrombosis or pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
158
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(172 citation statements)
references
References 30 publications
10
158
0
4
Order By: Relevance
“…Another study by Rosengren et al [20]it showed that SES variables such as persistent stress and low occupational class were independently related to future PE, while no such significant relationship could be demonstrated between DVT and SES [20]. It is also important to note that this study [20], which to the best of our knowledge is the only that has evaluated possible associations of this kind, was performed in male subjects only.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Another study by Rosengren et al [20]it showed that SES variables such as persistent stress and low occupational class were independently related to future PE, while no such significant relationship could be demonstrated between DVT and SES [20]. It is also important to note that this study [20], which to the best of our knowledge is the only that has evaluated possible associations of this kind, was performed in male subjects only.…”
Section: Introductionmentioning
confidence: 77%
“…It is therefore of great interest to know whether variables reflecting the SES of an individual are related to the risk for VTE in the same way as has been shown for different manifestations of arterial vascular disease [4][5][6][11][12], In 1981, a study by Samkoff et al demonstrated an increased rate of PE in subjects with less than 8 years of education compared to in subjects with longer education [19]. Another study by Rosengren et al [20]it showed that SES variables such as persistent stress and low occupational class were independently related to future PE, while no such significant relationship could be demonstrated between DVT and SES [20]. It is also important to note that this study [20], which to the best of our knowledge is the only that has evaluated possible associations of this kind, was performed in male subjects only.…”
Section: Introductionmentioning
confidence: 99%
“…Women with trauma exposure who did not report PTSD symptoms also exhibited increased risk of VTE incidence compared to women with no trauma exposure, although the magnitude of elevated risk was not as substantial as for women with high PTSD symptom levels. Initial research has linked psychosocial factors, including chronic stress36 and depression,9, 10 to VTE risk. Our study further underscores the role that psychosocial variables may play in contributing to the development of VTE, and suggests that the experience of extremely stressful, traumatic events and related posttraumatic stress reactions may have even more widespread cardiotoxic effects than has previously been considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall diagnostic validity of the Swedish Inpatient Register is close to 90% [30]. Moreover, the diagnosis of VTE in the Swedish Inpatient Register has been validated and found to be correct in 95% of VTE diagnoses [46]. In addition, in 91% of cases, VTE is diagnosed by an objective method [46].…”
Section: Familial History and Unusual Forms Of Vtementioning
confidence: 99%